Salivary cardiac-enriched FHL2-interacting protein is associated with higher diastolic-to-systolic-blood pressure ratio, sedentary time and center of pressure displacement in healthy 7-9 years old school-children - Vasileva, Fidanka; Font-Lladó, Raquel; Carreras-Badosa, Gemma; Roman-Viñas, Blanca; Cadellans-Arróniz, Aïda; López-Bermejo, Abel; Prats-Puig, Anna (Frontiers in Endocrinology, 2024)
Introduction: Cardiac-enriched FHL2-interacting protein (CEFIP) is a recently identified protein, first found in the z-disc of striated muscles, and related to cardiovascular diseases. Our objectives are: 1) to quantify CEFIP in saliva in healthy 7-9 years old school-children; and 2) to assess the associations of salivary CEFIP concentration and blood pressure, physical (in)activity and physical fitness in these children. Methods: A total of 72 children (7.6±0.3 years) were included in the study, recruited in primary schools in Girona (Spain). A sandwich enzyme-linked immunosorbent assay was used (abx506878; Abbexa, United Kingdom) to quantify CEFIP in saliva. Anthropometric evaluation was performed [body mass, height and body mass index (BMI)]. Systolic and diastolic blood pressure were measured by means of an electronic oscillometer and the diastolic-to-systolic blood pressure ratio (D/S BP ratio) was calculated. Physical (in)activity [sedentary time and time spent in physical activity (PA)] were assessed by means of a triaxial Actigraph GT3X accelerometer (Actigraph, Pensacola, FL, USA) that children were instructed to wear for 24h during 7 conssecutive days. Finally, physical fitness (speed and agility, explosive power of legs, handgrip strength, flexibility and balance) were assessed through validated and standardized testing batteries. Results: CEFIP was easily detected and measured in all saliva samples (mean concentration: 0.6±0.2 pg/ml). Salivary CEFIP was positively associated with D/S BP ratio (r=0.305, p=0.010) and sedentary time (r=0.317, p=0.012), but negatively associated with PA in 7-9 years old school-children (r=-0.350, p=0.002). Furthermore, salivary CEFIP was related to lower level of balance i.e., higher center of pressure (CoP) displacement in these children (r=0.411, p<0.001). The associations of salivary CEFIP with D/S BP ratio (Beta=0.349, p=0.004), sedentary time (Beta=0.354, p=0.009) and CoP displacement (Beta=0.401, p=0.001), were maintained significant after adjustment for potential confounding variables such as age, gender and BMI in linear regression analyses. Conclusion: CEFIP can be easily assessed in saliva as a promising biomarker associated with cardiovascular health in 7-9 years old school-children. Interestingly, higher salivary CEFIP concentration was related to higher D/S BP ratio, more sedentary time and higher CoP displacement i.e., lower level of balance in these children.